Effectiveness of a web-based tobacco product use prevention videogame intervention on young adolescents' beliefs and knowledge. Issue 1 (2nd January 2021) - Hieftje, Kimberly D.; Fernandes, Claudia-Santi F.; Lin, I-Hsin; Fiellin, Lynn E.
Abstract: Background: Preventing tobacco product initiation in youth is a critical need. While cigarette smoking among youth has been on the decline, tobacco use in other forms, such as e-cigarettes and vaping, continue to be a major concern. The purpose of this study was to conduct a real-world, quasi-experimental test of the effectiveness of a web-based videogame, smokeSCREEN, aimed at developing healthy beliefs and knowledge associated with tobacco product use prevention, including electronic cigarettes. Methods: Adolescents ( N =  560) aged 10–16 years were enrolled from schools and afterschool programs in a single-group pre–post study. Measures included a pre- and post-survey of beliefs and knowledge about tobacco product use. At post-survey, participants were asked questions regarding their gameplay experience. Paired responses for the tobacco product use in the beliefs and knowledge survey before and after the smokeSCREEN videogame intervention were compared using McNemar's test. Descriptive statistics were generated to assess overall participant gameplay experience. Results: McNemar's test showed significant differences in the proportions of correct answers before (pre-survey) and after (post-survey) the intervention in seven out of eight belief questions ( p  < . 0001). It also suggested significant differences in the proportions of correct answers before (pre-survey) and after (post-survey) the intervention in all six knowledge questions ( p  < . 0001). Several gender and age differences were noted for belief and knowledge questions related to e-cigarettes and vaping. There was no association between gameplay duration at post-survey or to the answers of the beliefs or knowledge questions. Overall, participants reported that they enjoyed playing the game. Conclusions: Findings suggest that the videogame intervention, smokeSCREEN, has a promising effect on participants' beliefs and knowledge about tobacco product use, including electronic cigarettes and vaping, and is well accepted by adolescents.